DOI: 10.22215/etd/2014-10536
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Attitudes Towards Violence and Violent Behaviour: The Use of Implicit and Self-Report Measures

Abstract: The current studies investigated the relationship between attitudes towards violence and violent behaviour. Violent attitudes have mostly been assessed with self-report measures. Within social psychology, implicit attitudes have also been assessed using response latency measures finding significance regarding these attitudes. The current studies examined implicit and self-report attitudes, as well as the relationship between attitudes and past/future violence, among three studies (one containing offenders). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 54 publications
(195 reference statements)
1
9
1
Order By: Relevance
“…Regardless, these bivariate results contrast most studies to date that T A B L E 3 Significant hierarchical multiple linear regression analysis assessing incremental validity accounted for by VE-IAT. have assessed implicit attitudes in relation to violent outcomes, excluding IPV or sexual aggression (e.g., Maimone, 2014;Polaschek et al, 2010;Zwets et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless, these bivariate results contrast most studies to date that T A B L E 3 Significant hierarchical multiple linear regression analysis assessing incremental validity accounted for by VE-IAT. have assessed implicit attitudes in relation to violent outcomes, excluding IPV or sexual aggression (e.g., Maimone, 2014;Polaschek et al, 2010;Zwets et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Research on the validity of implicit attitudes as a predictor of aggressive behaviour has produced mixed findings (McCormick, 2013). Indeed, some authors have found support for the use of implicit measures as they apply to the prediction of aggressive behaviours (e.g., Banse & Fischer, 2002), whereas others have found that explicit, self-report measures of attitudes are stronger predictors of aggression than implicit attitudes (e.g., Maimone, 2014). Banse and Fischer (2002) developed a modified version of the IAT, the "Aggressiveness-IAT" to examine the predictive validity of implicit measures of aggressiveness as they applied to physically aggressive behaviours of hockey and volleyball players.…”
Section: Iat and Aggressive Behaviourmentioning
confidence: 99%
“…Lastly, Maimone (2014) conducted three studies examining implicit and explicit attitudes toward violent behaviour among two samples of male undergraduate students and one sample of adult offenders. The first study examining attitudes toward violence among male university students found that only explicit (and not implicit) attitudes toward violence differentiated students who reported engaging in violence from those who had not.…”
Section: Iat and Aggressive Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…Implicit attitudes are important in understanding and predicting violent behaviour (e.g., Eckhardt & Crane, 2014;Eckhardt et al, 2012;Hermann & Nunes, 2018;Maimone, 2021), and have been shown to explain and predict violent behaviour differently than explicit attitudes (e.g., Eckhardt & Crane, 2014;Eckhardt et al, 2012;Maimone, 2014Maimone, , 2021. Future research should seek to examine the temporal stability of implicit attitudes toward violence, specifically, and should explore the best approaches to changing them.…”
Section: Future Directionsmentioning
confidence: 99%